A Lithuanian in Paris: Between Mania and Philia - Bikulčius, Vytautas (Literatūra, 2016)
The paper deals with the situation of a Lithuanian in Paris, in other words, the image of the capital of France presented in the travel books “Letters from Paris” (1937) of Antanas Vienuolis, “The Fair of Illusions” (1983) of Laimonas Tapinas, “Letters from Paris” (2007) of Rimantas Vanagas and “The Paris Diary” (2013) of Jaroslavas Melnikas.The paper draws on the methodology of imagology, according to which mania is identified when the writer perceives foreign reality as superior to national culture. Phobia, contrary to mania, is identified when national culture is valued more than foreign reality. Philia is identified when the writer perceives foreign and national culture identically. Idiocracy is identified when the writer presents his own attitude towards foreign reality.Despite changes in the historical context, the image of Paris remains mainly attractive and may be identified as philia. Some evidences of philia may be found in the books of A. Vienuolis, L. Tapinas, R. Vanagas, J. Melnikas although the time span between the publication of the first and the last book is about 80 years. No matter that the historical context is very different (e.g., the book of A. Vienuolis was published before World War II) it is not the main factor that would determine the priority of one culture over another.Several but not many evidences of mania or phobia may also be detected and it shows that the impressions of the authors are not onetime or hasty. The evidences of mania or phobia may be found in the books of A. Vienuolis, R. Vanagas, J. Melnikas. Still different cultural experiences, different potential of France as one of the main countries in the world undoubtedly contribute to the arousal of the above attitude. On the other hand, phobia proves that each country, even the smallest one, has specific features which are worth appreciating and even put it above others.Whereas the author, who came to Paris in the Soviet era, inevitably had to adapt to the norms of the ideology of his country or his impressions would be censored. That is especially evident in the book of L. Tapinas “The Fair of Illusions”; the truth is that although the author paid some tribute to the dominant ideology he managed to express his own attitude which is close to philia and idiocracy. It is clear that such tribute to ideology was used as a lightening rod so as to divert attention of censorship from particular matters (for instance, activity of Lithuanian artists in Paris before WW II) that the author intended to tell in his book.J. Melnikas, whose stay in Paris was longest, not only withstands any hasty valuations but also manages to express his own attitude, idiocracy, which draws on optimism. It is not a coincidence that in the subtitle this book of impressions is defined as the “optimist’s handbook”.
Keywords: imagology; philia; mania; phobia; idiocracy